Economic efficiency and supply response of women as farm managers: comparative evidence from Western Kenya - Alene, A.; Manyong, Victor M.; Omanya, G.; Mignouna, H.; Bokanga, M.; Odhiambo, G.D. (Elsevier, 2008)
This paper assessed the relative economic efficiency and output supply and input demand responses of women farmers in western Kenya. The results showed that women are as technically and allocatively efficient as men. However, neither men nor women have absolute allocative efficiency. Women farmers are equally responsive to price incentives in terms of output supply and input demand. While education and extension contact have significant effects on overall maize supply and input demand, only extension contact has significant effects among women farmers. The paper discusses a number of significant results and concludes with implications for policy.